Collagen and reticular fibers in left ventricular muscle in diabetic rats: Physical exercise prevents its changes? - Castellar, A. [UNESP]; Remedio, R. N. [UNESP]; Barbosa, R. A. [UNESP]; Gomes, R. J.; Caetano, Flávio Henrique [UNESP] (Churchill Livingstone, 2011)
Diabetic cardiomyopathy contributes to the high incidence of mortality in both types of diabetes. We aimed to investigate the histochemical aspects of collagen and reticular fibers in the cardiac muscle and evaluate the influence of physical exercise on these aspects. Wistar rats were divided in 4 groups: sedentary control (SC), trained control (TC), sedentary diabetic (SD) and trained diabetic (TD). Diabetes was induced with alloxan (35 mg/kg). Training program consisted of swimming 1 h/day with a load of 4.8% of body weight for TD and 5.2% for TC. during 8 weeks. At the end of the experiment, samples of the left ventricle were collected, fixed in Bouin and processed on historesin. Sections were stained with periodic acid of Schiff, picrosirius-hematoxylin and ammoniacal silver. The PAS technique shows that individuals of group SD presented more intense reaction that the other groups. Picrosirius-hematoxylin technique showed a possible deposition of collagen fibers in SD. The TD group presented a reaction a lot similar to the controls' for both techniques', showing a possible prevention of this deposition. These results indicate that physical exercises might have an important role on the prevention of some negative alterations caused by experimental diabetes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Diabetes mellitus; Myocardium; Exercise; Histochemistry; Alloxan